2021
DOI: 10.3389/fpls.2021.672023
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Kalanchoë blossfeldiana, Containing Individual rol Genes and Open Reading Frames Under 35S Promoter, Exhibit Compact Habit, Reduced Plant Growth, and Altered Ethylene Tolerance in Flowers

Abstract: Reduced growth habit is a desirable trait for ornamental potted plants and can successfully be obtained through Rhizobium rhizogenes transformation in a stable and heritable manner. Additionally, it can also be obtained by transformation with Agrobacterium tumefaciens harboring specific genes from R. rhizogenes. The bacterial T-DNA harbors four root oncogenic loci (rol) genes and 14 less known open reading frames (ORFs). The four rol genes, i.e., rolA, rolB, rolC, and rolD, are conceived as the common denomina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 113 publications
0
11
0
Order By: Relevance
“…The dwarfing and well-branched phenotypes observed in the present study indicate reduced apical dominance of rolC-OX plants (Figure 1A-C), an effect that was also seen in carnation and tobacco plants overexpressing rolC (Eva Casanovaa 2003). It has been previously speculated that over-expression of rolC may lead to increased CTK levels (Favero et al 2021), a feature that might contribute to the phenotypes observed here. In general, high ratios of CTKto-auxins promote plant shoot differentiation (Naseem et al 2012); however, here, the gene expression data did not support the idea based on the CTK transcript levels.…”
Section: Improved Stress Resistance and Enhanced Aba Accumulation In ...mentioning
confidence: 62%
See 3 more Smart Citations
“…The dwarfing and well-branched phenotypes observed in the present study indicate reduced apical dominance of rolC-OX plants (Figure 1A-C), an effect that was also seen in carnation and tobacco plants overexpressing rolC (Eva Casanovaa 2003). It has been previously speculated that over-expression of rolC may lead to increased CTK levels (Favero et al 2021), a feature that might contribute to the phenotypes observed here. In general, high ratios of CTKto-auxins promote plant shoot differentiation (Naseem et al 2012); however, here, the gene expression data did not support the idea based on the CTK transcript levels.…”
Section: Improved Stress Resistance and Enhanced Aba Accumulation In ...mentioning
confidence: 62%
“…The rol C sequence was amplified from the total DNA of R. rhizogenes A4 strain (ATCC43057) (Favero et al 2021) on a MyCycler (Biorad) using TaKaRa LA Taq polymerase (Mountain View). The amplification product was BP‐cloned into the entry vector pDONR221 and subsequently recombined with the destination vector pK2GW7 to generate 35S:rol C fusion constructs according to Favero et al (2021).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Later, F1 plants were inbred and it was found that the same correlation between the presence of rol-genes and compactness continued in the obtained F2 plants (Lütken et al, 2012b). Moreover, the study of individual rol genes and less characterized open reading frames from R. rhizogenes have very recently been shown to present higher ethylene tolerance in transgenic lines containing 35S::ORF14 (Favero et al, 2021).…”
Section: Genetic Transformationmentioning
confidence: 92%